2016
DOI: 10.1038/srep34400
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and in-vivo Nano-Endoscopy

Abstract: Analysis of individual cells at the subcellular level is important for understanding diseases and accelerating drug discovery. Nanoscale endoscopes allow minimally invasive probing of individual cell interiors. Several such instruments have been presented previously, but they are either too complex to fabricate or require sophisticated external detectors because of low signal collection efficiency. Here we present a nanoendoscope that can locally excite fluorescence in labelled cell organelles and collect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These technologies will revolutionize in vitro assays and allow simple, non-invasive, inexpensive devices for patient-performed in-home diagnostics. A limiting factor off the chip technologies is that they only allow extracellular and surface-cellular detection, but another biosensing technology called nanoscale endoscopes allows subcellular detection of organelles and cytoplasmic biomarkers (82). The endoscope non-invasively probes a cell and photonically stimulates fluorescently tagged organelles to detect diseased cells based on individual intracellular signals (82).…”
Section: Nano-enabled Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These technologies will revolutionize in vitro assays and allow simple, non-invasive, inexpensive devices for patient-performed in-home diagnostics. A limiting factor off the chip technologies is that they only allow extracellular and surface-cellular detection, but another biosensing technology called nanoscale endoscopes allows subcellular detection of organelles and cytoplasmic biomarkers (82). The endoscope non-invasively probes a cell and photonically stimulates fluorescently tagged organelles to detect diseased cells based on individual intracellular signals (82).…”
Section: Nano-enabled Diagnosticsmentioning
confidence: 99%
“…A limiting factor off the chip technologies is that they only allow extracellular and surface-cellular detection, but another biosensing technology called nanoscale endoscopes allows subcellular detection of organelles and cytoplasmic biomarkers (82). The endoscope non-invasively probes a cell and photonically stimulates fluorescently tagged organelles to detect diseased cells based on individual intracellular signals (82). This technique provides insight into intracellular disease profiles, which will significantly aid in the development of future therapies.…”
Section: Nano-enabled Diagnosticsmentioning
confidence: 99%
“…Transplantation of cells, microvesicles, microRNAs, and other molecules has encouraged the incorporation of peripheral therapeutic targets in organs other than the brain 7–10 . Characterizing gut and brain microbiomes, in addition to microbiomes located in other organs, using single‐cell omics and transcriptomics 11,12 will be the first step in elucidating the stroke pathology and progressing cell‐based therapeutic strategies along with other neurological diseases 7 . Furthermore, Parkinson's disease (PD) models have recently revealed the use of potent microbiomes both as a biomarker and therapeutic target, 13,14 shifting from brain‐focused neurological diagnosis and treatments to analysis of peripheral in the progression of PD 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In cell endoscopy, small sub-micrometer probes such as glass pipettes, glass fibers, carbon nanopipettes, carbon nanotubes, nanowires, and atomic force microscopic tips are inserted into a cell noninvasively to perform various tasks such as intracellular sensing, delivery, plasmon phototherapy, electrochemistry, and electrophysiology at different locations of the cell with high spatial resolution. A particular cell endoscopy probe utilizes surface enhanced Raman spectroscopy (SERS), owing to its superb sensitivity for detection of biochemicals in and around cells. As proof of concept, Vitol et al demonstrated that the positioning of the 150 nm tip of a SERS-active glass pipette in the nucleus or in the cytoplasm of a HeLa cell yields clearly distinguishable spectra associated with both DNA and protein in the nucleus and the absence of DNA in the cytoplasm . Using a similar SERS nanopipette extracellularly, Lussier et al showed that the metabolic process of a living Madin–Darby canine kidney epithelial cell can be monitored in situ through the SERS detection of several metabolites .…”
Section: Introductionmentioning
confidence: 99%